Análise de viabilidade para implantação de linhas transmissão em HVDC - Santana, Leonardo Batista de (2019)
With the evolution of industry and society itself, energy consumption has risen to levels never before seen. As a result, the electrical system began to undergo an adaptation in order to overcome the requested loads. At the same time, the benefits that the use of the direct current load transport pattern would be brought to the whole system. However, this type of discussion brings the reassessment of our entire modern electrical system. This work aims to deal in a technical way, which are the needs, viabilities and benefits that the system in direct current can bring to the present day. Although HVDC systems cost more to HVAC systems, the study concludes that there are enough advantages to enable them to be made economic and technical reductions. With regard to the economic aspect, DC systems have better transmission efficiency, and thus less investment for long-distance lines. In relation to the technical questions, HVDC systems have better control of power flow, flexibility of operation, and control of systemic parameters. Thus, the main result obtained shows that HVDC technology has been becoming one of the main energy efficiency techniques for power systems.